The dialects languages and Arab words cited by Alsaheb Bin Abbad (D. 385 H) in Al-Muheet's dictionary of the language = اللهجات واللغات وأقوال العرب التي استشهد بها الصاحب بن عباد (ت 385ه) في معجم المحيط في اللغة - Alshahri, Mohammed Albakhit Said; Haji Ibrahim, Majdi; Ali, Asem Shehadeh Saleh (International Organization Center of Academic Research, 2020)
تتابع هذ الدراسة اللهجات التي أوردها واستشهد بها ابن عباد في معجمه الصاحب في اللغة، ودراسة تحليلية للمواد والشروح التي تناثرت في ثنايا المعجم. تكمن المشكلة في أن الدراسات التي ناقشت ووافقت على كتاب معجم المحيط في اللغة لم تستجل المنهج الذي استعمله ابن عباد في الموضوعات والقضايا التي طرحها بين دفات معجمه، إذ لم يحظ هذا الجانب بدراسة متعمقة؛ لذا تهدف الدراسة إلى بيان منهجه في الاستشهاد باللهجات واللغات، وعرض منهج في الاستشهاد بالشواهد الشعرية وأقوال العرب من خلال المنهج الوصفي وتحليل وتعليل وإحصاء اللهجات. توصلت الدراسة إلى النتائج الآتية: كان لذكر اللهجات العربية المتنوعة جعل اللهجات داخل معجم المحيط بي اللغة كيانا يستحق الدراسة والتحليل، واستشهد الصاحب بن عباد خلال شرحه للمواد للعديد من اللغات واللهجات؛ حيث كان أكثرها ورودا لغة هذيل 40 مرة، ثم أهل اليمن 34 مرة، ولغة أهل فارس 28 مرة، ولغة حميلا 20 مرة، وقلل الصاحب بن عباد من الاستشهاد بالأشعر العربية. ****************************************************************************** This study follows the languages and dialects mentioned and cited by Ibn Abbad in his surrounding dictionary on the language, and an analytical study of the materials and explanations that were scattered throughout the dictionary. The problem lies in the fact that the studies that were discussed and stood on the book “The Lexicon of the Ocean in Language” did not record the approach used by Ibn Abbad in the topics and issues that he brought up between the books of his lexicon, as this aspect did not receive an in-depth and careful study. Therefore, the study aims to: Explain his method in citing dialects and languages, and present his method in citing poetic evidence and sayings of the Arabs. Through the descriptive method, analysis, explanation and statistics, the study reached the following results: The mention of the various Arabic dialects has made the Arabic dialects within the ocean dictionary in the language an entity worthy of study and analysis. Al-Saheb bin Abbad was martyred during his explanation of the materials for many languages and dialects, as the most roses were Hudhayl's language 40 times, then the people of Yemen 34 times, the language of the people of Persia 28 times and the language of Hamir 20 times. Al-Saheb Bin Abbad reduced his citation to Arabic poetry.